Teaching Foreign Languages Through Culture - Omeri, Arti (European Journal of Multidisciplinary Studies, 2016)
The word is becoming globalized in every aspect. As a result, people are encountering everyday many foreign languages and cultures either through mass media, social media, schools, books etc. Living in this type of environment gives us the opportunity to learn and study many foreign languages and cultures. The importance of the relation between language and culture has been studied and assessed since a long time. This study is focused on how foreign languages are taught through culture. There can be raised several important question regarding the relation between language and culture. Is there any connection between language and culture? Do they influence one another? Can someone learn a language without knowing the culture and vice versa? In order to answers such questions there was revised the most modern literature on this topic. After revising the literature, a survey was also conducted to the lecturers and students of foreign languages faculty at “Aleksander Xhuvani” University in Elbasan. The purpose was to approach the topic from both perspectives and get the results and opinions from different point of views. The number of students participating in the survey was higher than lecturers, so percentages are given separately for both categories. Then the results were analyzed and compared with one another
Keywords: Language, Culture, Foreign languages, Effective communication, Cultural barriers, Education.